Increasing knowledge and early detection of cervical cancer in women of childbearing age through IVA examination - Asridawati Akib; Sri Wahyuni; Rukina Rukina; Rosmiaty Pammu; Ria Wahyuni; Frynadia Lele; Alysia Pramesti Tunggadewi (Lembaga Penelitian dan Pengabdian Masyarakat,Politeknik Sandi Karsa, 2024)
Cervical cancer is one of the cancers that has a high prevalence in women, especially in childbearing age. Early detection through Visual Inspection of Acetic Acid (IVA) is an effective method to reduce the incidence and mortality rate due to cervical cancer. This Community Service Activity (PKM) aims to increase the knowledge of women of childbearing age about the importance of early detection of cervical cancer and facilitate IVA examinations for them. The methods used include health counseling through interactive lectures, distribution of educational materials, and the implementation of free IVA examinations. The results of the activity showed a significant increase in participants' knowledge about cervical cancer and the importance of early detection. In addition, enthusiasm and participation in IVA examinations increased, with more than 80% of participants attending undergoing examinations. This activity is expected to contribute to reducing the incidence of cervical cancer through preventive and educational efforts. A continuation of this program is the establishment of support groups in the community that will continue to promote reproductive health and early detection of cancer.